Managing Local Stressors for Coral Reef Condition and Ecosystem Services Delivery Under Climate Scenarios - Weijerman, Mariska; Veazey, Lindsay; Yee, Susan; Vaché, Kellie; Delevaux, Jade M. S.; Donovan, Mary K.; Falinski, Kim; Lecky, Joey; Oleson, Kirsten L. L. (Frontiers in Marine Science, 2018)
Coral reefs provide numerous ecosystem goods and services, but are threatened by multiple environmental and anthropogenic stressors. We used a spatially-explicit biophysical ecosystem model to evaluate socio-ecological trade-offs of land-based versus marine-based management scenarios, and local-scale versus global-scale stressors and their cumulative impacts. To increase the relevance of understanding ecological change for the public and decision-makers, we used four ecological production functions to translate the model outputs into the ecosystem services: “State of the Reef’, “Trophic Integrity”, “Fisheries Production,” and “Fisheries Landings”. For a case study of Maui Nui, Hawaiʻi, land-based management attenuated coral cover decline whereas fisheries management promoted higher total fish biomass. Placement of no-take marine protected areas (MPAs) across 30% of coral reef areas led to a reversal of the historical decline in predatory fish biomass, although this outcome depended on the spatial arrangement of MPAs. Coral cover declined less severely under strict sediment mitigation scenarios. However, the benefits of these local management scenarios were largely lost when accounting for climate-related impacts. Climate-related stressors indirectly increased herbivore biomass due to the shift from corals to algae and, hence, greater food availability. The two ecosystem services related to fish biomass increased under climate-related stressors but “Trophic Integrity” of the reef declined, indicating a less resilient reef. “State of the Reef” improved most and “Trophic Integrity” declined least under an optimistic global warming scenario and strict local management. This work provides insight into the relative influence of land-based versus marine-based management and local versus global stressors as drivers of changes in ecosystem dynamics while quantifying the tradeoffs between conservation- and extraction-oriented ecosystem services.